2016
DOI: 10.1111/edt.12275
|View full text |Cite
|
Sign up to set email alerts
|

Difference among shock‐absorbing capabilities of mouthguard materials

Abstract: These results suggest that all of the commercially available mouthguard sheet materials had high shock-absorbing capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…Polyolefin exhibits satisfactory physical properties such as lower water absorption and better adhesive strength which is important when laminating the materials in comparison with ethylene vinyl acetate, and is suitable for use as mouthguard material . Recently, it has been reported that mouthguard materials such as ethylene vinyl acetate and polyolefin had high shock absorbing capabilities . However, the change of sheet temperature during heating of polyolefin has not been determined, and the appropriate heating conditions for polyolefin have also not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefin exhibits satisfactory physical properties such as lower water absorption and better adhesive strength which is important when laminating the materials in comparison with ethylene vinyl acetate, and is suitable for use as mouthguard material . Recently, it has been reported that mouthguard materials such as ethylene vinyl acetate and polyolefin had high shock absorbing capabilities . However, the change of sheet temperature during heating of polyolefin has not been determined, and the appropriate heating conditions for polyolefin have also not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Fukasawa et al observed that the load absorbency of 12 commercial MG materials ranged between 26-37% compared with that of the control group; the MIF-t values of the commercial sheets ranged between 0.42-0.62 ms, and that of the control group was 0.39 ms 18) . Our results revealed that the shock absorbency of TAE was not significantly different from that of ERK and other commercial materials that were reported previously by Fukasawa et al 18) .…”
Section: Free-falling Ball Impact Testmentioning
confidence: 99%
“…A shock absorption test was conducted based on a previously reported method 18) . The specimens were disks of TAE, ERK, and a control (i.e., without material), which were 2 mm in thickness and 50 mm in diameter.…”
Section: Free-falling Ball Impact Testmentioning
confidence: 99%
See 2 more Smart Citations